PEMBERIAN CAHAYA TAMBAHAN DENGAN LAMPU HID DAN LED UNTUK MERESPON WAKTU PEMBUNGAAN TOMAT CHERRY (Solanum Liycopersicum var cerasiforme) DI DALAM RUMAH TANAMAN - Anugrah R. Sandag; D. Ludong; H. Rawung (COCOS, 2017)
ABSTRACT Extreme climate change is one of the factors that determine the quality of the plant. In this case one of the main factors driving plants to photosynthesise is light. (Alhadi, 2016). In general, the provision of ideal conditions is still limited to the protection of plants from extreme weather using greenhouse or better known as the greenhouse or plant house. Plant house is one way to provide an environment closer to the optimum conditions for plant growth. According to (Fides, 1992) the addition of artificial light to create long day conditions in the equator area of about 3-4 hours with the intensity of light with a range of 32-108 lux. Long day manipulations can be made using light from both incandescent and tube lamp sources (Kofranek, 1980). The purpose of this research is to study the substitution of sunlight with HID (High Intensity Discharge) lamp and LED (Light Emiting Diode) to optimize the growth of Cherry tomato plant in tropical plant house made from polyethylene (PE) roof. The results showed that the total intensity of light inside the plant house was obtained from the total intensity of the incoming sunlight in the plant house plus the total HID light bulb that is equal to 217.86 MJ/ m2 (treatment N2) and total sunlight plus total LED lamp light that is equal to 208.58 MJ / m2 (N3 treatment). But the intensity of this light is still much smaller than the total intensity of light outside the plant house (treatment N0) that is equal to 526.65 MJ / m2